Notas de um naturalista do sul do Brasil: Fritz Müller ; história da ciência e contribuições para a biologia - Souza, Flavia Pacheco Alves de (Online access: OAPEN DOAB Directory of Open Access Books., 2017)
"This book is a biographical construction of Fritz Müller (1822-1897), a German naturalist residing in Brazil during the 19th century. Fritz Müller published 264 works throughout his life (these were originally sent as letters to several correspondents and later published as scientific articles), mostly on subjects related to evolution, fauna, flora and ecology. Müller adopted Brazil as his homeland and the colony of Blumenau as his home. After coming to Brazil, he never returned to Europe and confided in his friends for letters that he didn't trade his country life for the “civilized” life he could have in Germany. Not even Rio de Janeiro, capital of the Empire and stronghold of Brazilian science at the time, was visited by him. When, in 1891, while still an employee of the National Museum of Rio de Janeiro, the regulations began to require traveling naturalists to move their residence to the city, Müller did not hesitate to ask for his resignation from the position. His works, carried out in the province of Santa Catarina, Brazil, appeared in scientific journals (German and English) at the time and in communications made by third parties in scientific societies in England. In addition to corresponding with Charles Darwin (1809-1882), he corresponded with other well-known researchers in world science: Ernst Haeckel (1834-1919), Alexander Agassiz (1835-1910), Max Schultze (1825-1874), Raphael Meldola (1849-1915), Hermann Hagen (1817-1893) etc. Darwin asked Müller to write about his impressions and life in Santa Catarina, something like a book of narratives about the fauna and flora of the place. He even suggested titles, such as: Jornal de um naturalista do Brasil or Notes from a naturalist in Brazil. Despite his friend's insistence, Müller never made such a request. The title of this book is a tribute to the friendship between these two naturalists. Although these Notes were not written by Müller as Darwin wished, the objective is to present part of Müller's works carried out in Brazil, which had as scenery and characters elements of the fauna and flora of Santa Catarina. Thus, seeking to situate the importance of this knowledge for the history of contemporary biology. Finally, this book is not intended to exhaust the subject. Rather, it seeks to revisit Müller's work as a contribution to the history and memory of science in Brazil."